(untitled) (Research, Society and Development, 2022)
The coffee crop is nutritionally demanding, so it is essential to seek efficient fertilizers in providing nutrients. The increase in demand for the consumption of specialty coffees, traceability and sustainable practices makes farmers seek new technologies for the implementation of their crops, with products that promote plant growth of natural origin being quite relevant from an environmental point of view, especially those to based on seaweed extracts, however it is necessary to evaluate its agronomic efficiency in different crops. In this sense, the objective was to evaluate the effect of the seaweed extract of the species Ascophyllum nodosum on the initial growth of coffee trees. The research was carried out in Cordislândia-MG, in a targeted manner with three treatments applied via the foliar route with a 5 L manual sprayer, using different doses of a fertilizer based on seaweed extracts, as follows: T1 – 0 control, T2 – 500 mLha-1 (from the commercial product) and T3 –1000 mLha-1 (from the commercial product), applied 4 times, with an interval of 40 days between applications. The experiment was installed in a randomized block design (DBC), containing 3 treatments and 7 replications, where each plot consisted of 8 coffee seedlings, totaling 21 experimental units. The following parameters were evaluated: leaf area index, shoot length, root system length, stem diameter, total fresh mass, total dry mass and the ratio of root system to shoot. The treatments that received foliar applications of commercial liquid extracts of the seaweed Ascophyllum nodosum at a dose of 1000 mL.ha-1 obtained significant increments in shoot length, leaf area index, total fresh mass, total dry mass and root system ratio with shoots, statistically differing from the control treatment and from treatment 2, where the applied dose was 500 mL.ha-1.